Skin prick tests reveal stable and heritable reduction of allergenic potency of gene-silenced tomato fruits - Sonnewald, Uwe; et al. (Journal of Allergy and Clinical Immunology, 2006)
Clinical implications: Allergen-reduced plant foods might allow reduction of dietary restrictions for patients allergic to panallergen families.
Keywords: gene silencing; RNA interference; food allergy; tomato; Lyc e 3; allergenic potency; hypoallergenic; genetically modified food